Rouard's method as a modelling tool for the sensing characteristics of complex fibre Fabry-Perot interferometers formed between chirped fibre Bragg gratings - Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2005)
Phase and spectral response characteristics of fibre Fabry-Perot interferometers (FFPI), formed between linearly chirped fibre Bragg gratings (FBG), were theoretically modelled using Rouard's method. The method models accurately the phase shift through a complex grating structure which the transfer matrix model is unable to achieve. The FBG FFPI cavities were modelled with variable free spectral range that was tailored further to provide strain insensitivity and strain enhancement by making the chirp parameter and cavity length satisfy the desired conditions at a given wavelength of illumination.
Keywords: fibre Bragg grating; chirp; rouard's method; fibre Fabry-Perot; sensors; strain